If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 13 = -11 Reorder the terms: 13 + 3t = -11 Solving 13 + 3t = -11 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 3t = -11 + -13 Combine like terms: 13 + -13 = 0 0 + 3t = -11 + -13 3t = -11 + -13 Combine like terms: -11 + -13 = -24 3t = -24 Divide each side by '3'. t = -8 Simplifying t = -8
| 5x-25=2x+114 | | 18-3r=24 | | 5-7n+2n=-2n+2n | | 9y-(-22)=58 | | n-11=68 | | -11h-7=-18 | | 20x+10x=180 | | 4x^2-x+15=0 | | n-8=75 | | 4-2y=2y+13 | | 5y-20=-45 | | 6k+5=23 | | 6x+3=4x-11 | | 4q-17=2q+17 | | 3(2m+11)=33 | | 2y+11=4 | | x(x+1)+(x+2)=90 | | 5p-6=2p+12 | | 19-15x+26=180 | | -6x-2=10 | | 6x+8x+10x=120/24 | | 11r-21+-2r=-42 | | -2(2x+10)=180 | | 2x+9-5x=-27 | | 3r-31+5r=9 | | 2x-5x=90 | | 50-12=-7x+5x | | 6/8=12/x | | 1/2x+3x=96 | | -2q+42=-6 | | 2(x+1)+2.5=38 | | 14x^2=131 |